The impact of finance on the performance of Thai manufacturing small and medium-sized enterprises - Yot Amornkitvikai; Charles Harvie (Asian Development Bank Institute (ADBI), 2016)
This study sheds light on small and medium-sized enterprise (SME) financing and its performance in Thailand. It elaborates on the key sources of finance existing for Thai manufacturing SMEs and their importance for SME performance as measured by technical efficiency, export performance, and technological innovation. This study also examines the key factors enhancing SME access to external finance. Our results confirm that retained earnings are crucial to increase SME technical efficiency, but loans from unlicensed moneylenders deteriorate their export performance. For external finance, government-owned specialized financial institutions (SFIs) play a leading role in enhancing SME technical efficiency and export performance, but the results from the survey reveal that few Thai manufacturing SMEs actively seek external finance from these institutions. Foreign commercial banks also help enhance SME technical efficiency. The results show that larger SMEs have superior performance as measured by export performance and technological innovation performance. The results also reveal that financial institutions in Thailand still rely on collateral-based lending and SME financial transparency through audited financial statements to reduce asymmetric information and adverse selection costs.
Keywords: D22; D24; G20; L25; L60; 330; Thailand; manufacturing; SME; specialized financial institution; exports; export performance; technical efficiency; technology; innovation; market access; human resources; credit; financing; banks; business loans; collateral; interest rate